The Effect of Workplace Respect on Employee Performance: A Survey Study in Abu Ghraib Dairy Factory - Abdullah Mohammed, Atheer (Journal of Economics and Administrative Sciences, 2022)
This paper aims to explain the effect of workplace respect on employee performance at Abu Ghraib Dairy Factory (AGDF). For achieving the research aim, the analytical and descriptive approach was chosen using a questionnaire tool for collecting data. It covers 22 items; ten of them for the workplace respect variable and twelve items for the employee performance variable. The research population involved human resources who work at AGDF in Baghdad within two administrative levels (top and middle). We conducted a purposive stratified sample approach. It was distributed 70 questionnaire forms, and 65 forms were received. However, six of them had missing data and did not include in the final data analysis. The main results are that there is a positive significant effect of workplace respect on job performance. Moreover, workplace respect appears in AGDF through forgiving honest mistakes of workers. Furthermore, the sub-variable of the knowledge of work requirements ranked first in terms of availability, practice, attention, and adoption. Then followed by the dimensions (performance quality, the spent effort, and completed work) respectively. This can be understood that the availability of the three sub-variables combined has led to the factory owning a set of behaviors and functional activities. Paper type: Research paper.